DINAMIKA PEMBINAAN MANAJEMEN PEGAWAI NEGERI SIPIL PADA PEMERINTAHAN DAERAH (Studi Kasus Pemerintah Kota Balikpapan dan Kabupaten Kutai Kartanegara) - A., Rustan (Pusjar SKPP Lembaga Administrasi Negara, 2008)
The changes that occur more often in the law regulation about employee affairs nowadays demand the governments’ reaction to take the adjustment steps on the management building for the government apparatus in their region. Management building is one of the most important element to improve the work-performance of the local government apparatus which will lead to the implementation of service excellence for public society. Spaces for the innovation in management building for the government apparatus also need to be made so that autonomy function will not only bring prosperity for the society but also for the local government apparatus. Keywords: Management Building of the Government Apparatus, Local Governance